Creation of optical chains with prescribed characteristics. (1st March 2023) - Zeng, Yongxi; Yu, Yanzhong; Zhan, Qiwen
Abstract: We report a non-iterative method to create an arbitrarily spatially-orientated optical chain with prescribed characteristics through the use of antenna radiation theory and time reversal methodology. A pair of antennas consisting of an electric current line source (ELS) and a magnetic current line source (MLS) are employed to yield the required incident field pattern for 4 π focusing system. Numerical results demonstrate that the direction of the generated optical chain is consistent with the orientation of the combined antennas, and the length of the optical chain is approximately equal to the length of the combined antennas, and the amount, position and spacing of the dark hollow spots are determined by the length of the combined antenna and the amplitude periodic coefficient of the ELS. The generated optical chains may find potential applications in multi-points optical capture and particle delivery along prescribed directions.